Envoys must respect local laws - Eishan Jan, Mohammad Naqib (The New Straits Times Press (M) Bhd., 2017)
On March 4, Malaysia declared North Korean ambassador Kang Chol persona non grata and gave him 48 hours to leave the country. This article briefly explains the concept of persona non grata in the context of diplomatic relations in international law.